C-shaped canal configuration in lower molar - Case report - dos Santos, Lauren Grandi; Gallas, Amanda Nunes; Martos, Josué; Silveira, Luiz Fernando Machado (Brazilian Dental Science, 2015)
The C-shape configuration in molars it’s an anatomical variation that difficult the diagnosis and treatment. The aim of this study was to report a case of C-shape endodontic configuration in mandibular second molar. The radiographic examination of one patient revealed the extent of caries in the mesial aspect of mandibular second molar, without the presence of periapical lesion and was clinically noted the C-shape configuration of the root canal, extending from the mesiobuccal to the distal canal. Endodontic therapy was performed and after the root canal obturation with gutta-percha cones and endodontic cement the tooth was restored. We conclude that the anatomical condition in C-shape, although it brings many difficulties for the endodontic treatment, does not preclude the tooth rehabilitation.